A comprehensive analysis of the problems in sustainable construction and mitigation strategies - Bhadauria Alok; Rajani D.; Helena Raj Vijilius; Kalita Das Karabi; Dutt Amit; Ziara Sajjad (E3S Web of Conferences, 2024)
The challenges arising due to the construction industry in balancing the development along with ecological concerns are being focussed upon in this paper. The detailed analysis of the materials that are being brought to use as a sustainable material in the constructions sectors is being focussed upon. Since the late 20th century, there have been significant developments in the building industry. Since the population is rising and the need for housing is increasing, all available resources must be employed to satisfy the demand as it stands. This will have a significant long-term effect on the situation since the resources at hand are insufficient to meet the demand. There are many data and trends about sustainable construction approaches that is being developed by the researchers across the world that form the basis of this review study. The work found that associated industries should be encouraged to take part in the seminars, workshops, and other training programs that are organized at various events in order to deepen and improve their comprehension of the concept of sustainable development. The comparison drawn-out in between the conventional and a smart building concludes the benefits of using sustainable methods in the construction industry.